Radiation Characteristics of Guided and Leaky modes for a Plasma Column Antenna - Bo Yin (Institute of Advanced Engineering and Science, 2014)
A substantial problem for the radiation of a plasma column antenna is investigated. By means of the study on electromagnetic (EM) waves propagating along the plasma column and acting with plasma, it is found that a plasma column can radiate the EM energy when it works as two kinds of operation modes. The first one is a guided mode which leads to a surface current radiation, and its operation condition is obtained by determining the relation of plasma frequency and signal frequency. The second one is a leaky mode which causes a leaky wave radiation, and its operation condition is presented by analyzing normalized complex propagation constant. With further dealing with the leaky mode, its far field is got by applying the Schelkunoff’s equivalence principle on the surface of the plasma column. Radiation patterns of two kinds of modes are presented in their respective operation frequency bands, and reveal the radiation properties of the plasma antenna. The presented results are very helpful for further investigation in the design and application of plasma column antennaDOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3500